A case of membranoproliferative glomerulonephritis associated with psoriasis vulgaris - Marouane Jabrane; Abderrahim Wakrim; Mohammed Arrayhani (SpringerOpen, 2022)
Abstract Background Psoriasis is a chronic inflammatory disorder of the skin; the hallmark of psoriasis is sustained inflammation that leads to uncontrolled keratinocyte proliferation and dysfunctional differentiation. Psoriasis shows clear autoimmune-related pathomechanisms, in which autoantigen-specific T cells contribute to the development, chronification, and overall course of the disease. Psoriasis is primarily a skin disease, but other internal organs may be involved; affliction of the joints is well established, but kidney involvement is yet to be universally agreed upon, although some recent studies have linked psoriasis to kidney disease and certain glomerular diseases including secondary renal amyloidosis, Ig A nephropathy, and membranous glomerulopathy. Case presentation and conclusion In this paper, we report a case of primary membranoproliferative glomerulonephritis (MPGN) with nephrotic impure syndrome in a psoriatic patient. The etiological investigation was negative with normal serum complement and ASO titers and were negative for HBV, HCV, HIV, and ANA. The patient improved on prednisolone and angiotensin-converting enzyme inhibitors. To our best of knowledge, cases of MPGN associated with psoriasis are rare and we would like to shed light on this association.